Principles of macroeconomics - Greenlaw, Steven A.; Taylor, Timothy, 1960-; Shapiro, David, 1946-; BC Open Textbook Project; BCcampus; OpenStax College (OpenStax College, Rice University, 2017)
Principles of Macroeconomics 2e (2nd edition) covers the scope and sequence of most introductory economics courses. The text includes many current examples, which are handled in a politically equitable way. The outcome is a balanced approach to the theory and application of economics concepts. The second edition has been thoroughly revised to increase clarity, update data and current event impacts, and incorporate the feedback from many reviewers and adopters.
Welcome to economics! -- Choice in a world of scarcity -- Demand and supply -- Labor and financial markets -- Elasticity -- The macroeconomic perspective -- Economic growth -- Unenployment -- Inflation -- The international trade and capital flows -- The aggregate demand/aggregate supply model -- The Keynesian perspective -- The neoclassical perspective -- Money and banking -- Monetary policy and bank regulation -- Exchange rates and international capital flows -- Government budgets and fiscal policy -- The impacts of government borrowing -- Macroeconomic policy around the world -- International trade -- Globalization and protectionism -- The use of mathematics in principles of economics -- The expenditure-Output model -- Index.
Includes bibliographical references (pages 593-602) and index.
PDF, Second edition, MA2-2017-000-(10/17)-LC (viewed on 16 November, 2017).
Keywords: Macroeconomics -- Textbooks; Economics -- United States -- Textbooks; Electronic books